2004
DOI: 10.1203/01.pdr.0000145281.12853.9e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heme Oxygenase and Bilirubin in Oxidative Stress in Preterm Infants

Abstract: In a previous study, it was found that the decrease in the total plasma bilirubin level (Btot) in preterm infants was associated with the decrease in oxidative stress. We hypothesized that this occurs as a result of a pro-oxidant effect of heme oxygenase (HO), which outcompetes with the antioxidant properties of bilirubin. In this study we studied 12 preterm infants in whom the plasma levels of Btot, total hydroperoxide (TH), protein SH groups, HO activity, non-transferrin-bound iron (NTBI), and erythrocyte Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…34 In preterm infants, the expression of HO-1 is known to increase concurrently with a drop in total plasma bilirubin level and a reduction in total hydroperoxides, suggesting that HO-1 might play a role in reducing oxidative stress in premature infants. 35 Furthermore, HO-1 is thought to play an important role in retinal glial cells to protect photoreceptors from oxidative damage. 36,37 In this study, gene expression of HO-1 was increased in our model of ROP; however, the induction of HO-1 was not affected by the lack of GPx1.…”
Section: Discussionmentioning
confidence: 99%
“…34 In preterm infants, the expression of HO-1 is known to increase concurrently with a drop in total plasma bilirubin level and a reduction in total hydroperoxides, suggesting that HO-1 might play a role in reducing oxidative stress in premature infants. 35 Furthermore, HO-1 is thought to play an important role in retinal glial cells to protect photoreceptors from oxidative damage. 36,37 In this study, gene expression of HO-1 was increased in our model of ROP; however, the induction of HO-1 was not affected by the lack of GPx1.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies [68,69] found a substantially lower plasma oxidazibility in hyperbilirubinemic neonatal plasma than in normobilirubinemic adults. However, contradictory data have been reported [70,71].…”
Section: Contribution Of Bilirubin To Total Antioxidant Capacity Of Smentioning
confidence: 99%
“…Because the increased mortality observed in extremely preterm infants who are receiving PT and the injury to cell membranes and DNA by PT in in vitro studies suggest that it is prudent to use less intensive irradiance, it has been recommended to initiate PT at lower irradiance (standard PT), and to increase the level (intensive PT) only when TSB continues to rise . In addition, bilirubin is not only cytotoxic, it also has antioxidant effects for preterm infants, who are susceptible to oxidative stress …”
Section: What Are Standard and Intensive Pt?mentioning
confidence: 99%